2013
DOI: 10.1021/es400231x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Dissolution from Japanese Paddy Soil by a Dissimilatory Arsenate-Reducing Bacterium Geobacter sp. OR-1

Abstract: Dissimilatory As(V) (arsenate)-reducing bacteria may play an important role in arsenic release from anoxic sediments in the form of As(III) (arsenite). Although respiratory arsenate reductase genes (arrA) closely related to Geobacter species have been frequently detected in arsenic-rich sediments, it is still unclear whether they directly participate in arsenic release, mainly due to lack of pure cultures capable of arsenate reduction. In this study, we isolated a novel dissimilatory arsenate-reducing bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 55 publications
5
70
0
Order By: Relevance
“…An increased concentration of As(III) in soil solution is sometimes observed in flooded paddy fields (Takahashi et al 2004), suggesting that arsenic is dissolved from paddy soil. Although microbial activity can affect arsenic mobilization indirectly via reductive dissolution of iron (hydr)oxides associated with arsenic (Cummings et al 1999), numerous studies have revealed that As(V) reduction might be a key process controlling arsenic mobilization (Yamamura et al 2008;Ohtsuka et al 2013). Recently, Yamaguchi et al (2011) found that microbial activity was indispensable for reduction of As (V) to As(III), when two Japanese paddy soils were incubated under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An increased concentration of As(III) in soil solution is sometimes observed in flooded paddy fields (Takahashi et al 2004), suggesting that arsenic is dissolved from paddy soil. Although microbial activity can affect arsenic mobilization indirectly via reductive dissolution of iron (hydr)oxides associated with arsenic (Cummings et al 1999), numerous studies have revealed that As(V) reduction might be a key process controlling arsenic mobilization (Yamamura et al 2008;Ohtsuka et al 2013). Recently, Yamaguchi et al (2011) found that microbial activity was indispensable for reduction of As (V) to As(III), when two Japanese paddy soils were incubated under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of genes for As(V) respiration in several Geobacter genomes may enhance the As resistance of certain Geobacter species (Lear et al 2007;Giloteaux et al 2012;Hery et al 2008). Ohtsuka et al (2013) reported Geobacter sp. OR-1 isolated from Japanese paddy soil was a dissimilatory arsenate-reducing bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suppose that As(III) oxidation took place faster than As(III) adsorption at this concentration of As(III) (160 mM)and cells(10 9 CFU ml À1 ). In the case of microbial reduction, Huang et al and Ohtsuka et al indicated that the reduction of adsorbed As(V) is much slower than that of dissolved As(V) by As(V)-reducing bacteria (Huang et al, 2011b;Ohtsuka et al, 2013). They demonstrated that the presence of minerals hindered microbial As(V) reduction.…”
Section: Arsenic Adsorption In the Presence Of Bacteriamentioning
confidence: 99%
“…According to mechanisms of As(V) reduction in solid phase (Huang et al, 2011b;Ohtsuka et al, 2013), there might be two explanations of As(III) oxidation in solid phase: one is directly oxidation of As(III) in solid phase; one is that the attachment of cells promoted As(III) desorption, and the desorbed As(III) was oxidized followed by adsorption of As(V) on the solid phase (Dong et al, Fig. 3.…”
Section: Comparison Of As(iii) Oxidation In Three Cell-iron Oxide Sysmentioning
confidence: 99%